Empowering Student Creativity Through Problem-Based Learning Assisted by Assemblr Edu: A Study on Metamorphosis in Primary Science - Al-Zahra, Hawa Salsabila; Handayani, Sri Lestari (Journal of Educational Sciences, 2025)
This study aimed to investigate the impact of the Problem-Based Learning (PBL) model assisted by Assemblr Edu media on elementary students’ creativity in learning metamorphosis. Using a quantitative approach with a pretest-posttest control group design, student creativity was assessed through observation sheets focusing on fluency, flexibility, originality, and elaboration. The findings revealed that PBL supported by Assemblr Edu positively enhanced students’ creative abilities. The integration of augmented reality into PBL created a more engaging, interactive, and meaningful learning environment. Students were more active in problem-solving, expressing diverse ideas, and demonstrating original thinking. This approach also helped students better understand the concept of metamorphosis through hands-on exploration. The results suggest that combining PBL with interactive digital tools like Assemblr Edu can effectively support creative learning and improve science education at the elementary level, offering an innovative alternative for future teaching practices. Such integration not only motivates students but also fosters deeper engagement and long-term retention of scientific concepts.